Tuneable near white-emissive two-dimensional covalent organic frameworks - Li, Xing; Gao, Qiang; Wang, Juefan; Chen, Yifeng; Chen, Zhi-Hui; Xu, Hai-Sen; Tang, Wei; Leng, Kai; Ning, Guo-Hong; Wu, Jishan; Xu, Qing-Hua; Quek, Su Ying; et al. (Nature communications, 2018)
Most two-dimensional (2D) covalent organic frameworks (COFs) are non-fluorescent in the solid state even when they are constructed from emissive building blocks. The fluorescence quenching is usually attributed to non-irradiative rotation-related or π–π stacking-caused thermal energy dissipation process. Currently there is a lack of guiding principle on how to design fluorescent, solid-state material made of COF. Herein, we demonstrate that the eclipsed stacking structure of 2D COFs can be used to turn on, and tune, the solid-state photoluminescence from non-emissive building blocks by the restriction of intramolecular bond rotation via intralayer and interlayer hydrogen bonds among highly organized layers in the eclipse-stacked COFs. Our COFs serve as a platform whereby the size of the conjugated linkers and side-chain functionalities can be varied, rendering the emission colour-tuneable from blue to yellow and even white. This work provides a guide to design new solid-state emitters using COFs. Encoding functionalities in covalent organic frameworks (COFs) is important for widening their application field but the development of fluorescent COFs is hampered by a lack of guiding design principles. Here the authors demonstrate tuning and switching of the photoluminescence in 2D COFs made of non-emissive building blocks.